Cost-effectiveness of rivaroxaban versus apixaban for the initial treatment of venous thromboembolism and extended prevention of recurrences in the UK. (2nd November 2019) - Folkerts, Kerstin; Broughton, Julie; Sheikh, Usman; Mckaig, Sasha
Abstract: Aim: To evaluate the relative cost-effectiveness of using rivaroxaban vs apixaban for the initial treatment plus extended prevention of venous thromboembolism (VTE) in the UK. Extended prevention was assessed using a 10-mg rivaroxaban dose, as the 20-mg dose has already been evaluated. Methods: A Markov model compared the health outcomes and costs of treating VTE patient cohorts with either rivaroxaban (15 mg twice daily for 3 weeks, followed by 20 mg once daily for 6 months, then extended prevention with 10 mg once daily) or apixaban (10 mg twice daily for 1 week, followed by 5 mg twice daily for 6 months, then extended prevention with 2.5 mg twice daily) over a lifetime horizon. The model included an initial acute treatment and prevention phase (0–6 months) and an extended prevention phase (6–18 months). Efficacy and safety data were derived from two network meta-analyses. Reference treatment comparators were derived from the EINSTEIN-Pooled study and EINSTEIN-CHOICE trial. Healthcare costs and utility data were derived from published literature. Results: The rivaroxaban regimen was associated with increased quality-adjusted life years (QALYs) and slightly lower total costs compared with apixaban over a lifetime horizon. Deterministic and probabilistic sensitivity analyses demonstrated that rivaroxaban remained a cost-effective alternative to apixaban over a wide range of parameters. Incremental cost-effectiveness ratio estimates were below the £20, 000 per QALY threshold in 74.1% of 2, 000 model simulations. Scenario analyses further supported that rivaroxaban is a cost-effective alternative to apixaban. Limitations: Clinical and safety inputs were derived from network meta-analysis, which are subject to inherent limitations whereby small differences between study designs may severely impact efficacy and safety outcomes. Furthermore, these inputs were based on data from clinical trials, which may not reflect real-world data. Conclusions: Rivaroxaban was associated with a slightly lower total cost and increased QALYs compared with apixaban for VTE management in the UK over a lifetime horizon.